Viewing stromal vascular fraction de novo vessel formation and association with host microvasculature using the rat mesentery culture model. (18th May 2022) - Hodges, Nicholas A.; Lampejo, Arinola O.; Shang, Hulan; Rowe, Gabrielle; LeBlanc, Amanda Jo; Katz, Adam J.; Murfee, Walter L.
Abstract: Objective: The objective of the study is to demonstrate the innovation and utility of mesenteric tissue culture for discovering the microvascular growth dynamics associated with adipose‐derived stromal vascular fraction (SVF) transplantation. Understanding how SVF cells contribute to de novo vessel growth (i.e., neovascularization) and host network angiogenesis motivates the need to make observations at single‐cell and network levels within a tissue. Methods: Stromal vascular fraction was isolated from the inguinal adipose of adult male Wistar rats, labeled with DiI, and seeded onto adult Wistar rat mesentery tissues. Tissues were then cultured in MEM + 10% FBS for 3 days and labeled for BSI‐lectin to identify vessels. Alternatively, SVF and tissues from green fluorescent‐positive (GFP) Sprague Dawley rats were used to track SVF derived versus host vasculature. Results: Stromal vascular fraction‐treated tissues displayed a dramatically increased vascularized area compared to untreated tissues. DiI and GFP+ tracking of SVF identified neovascularization involving initial segment formation, radial outgrowth from central hub‐like structures, and connection of segments. Neovascularization was also supported by the formation of segments in previously avascular areas. New segments characteristic of SVF neovessels contained endothelial cells and pericytes. Additionally, a subset of SVF cells displayed the ability to associate with host vessels and the presence of SVF increased host network angiogenesis. Conclusions: The results showcase the use of the rat mesentery culture model as a novel tool for elucidating SVF cell transplant dynamics and highlight the impact of model selection for visualization.